Hanging Together, Together Hung? Career Implications of Interpersonal Ties Between CEOs and Top Managers - Stefan Hilger; Ansgar Richter; Utz Schäffer (BuR - Business Research, 2013)
Is it good or bad for senior executives to have strong interpersonal ties to the CEO? We argue that a strong relationship with the CEO raises the likelihood that a top manager stays in office or makes an upward career move when the CEO leaves office voluntarily. At the same time, such interpersonal ties also reinforce the negative spillover effects of a dismissal of the CEO on the career prospects of the manager concerned. Our empirical analysis lends support to both arguments. We contribute to managerial succession research by underlining the ambivalence of interpersonal ties within top management teams.
urn:nbn:de:0009-20-36441
Keywords: 650; corporate governance; interpersonal ties; top executive careers; top executive turnover; top management teams; Soziales Netzwerk; Karriereplanung; Führungskräfte; Corporate Governance